A catalog of the types of Staphylinidae (Insecta, Coleoptera) deposited in the Museo Argentino de Ciencias Naturales, Buenos Aires (MACN) - Bachmann, Axel O.; Chani-Posse, Mariana; Guala, Mariel E.; Newton, Alfred F. (Zootaxa, 2017)
The type specimens (all current categories) of Staphylinidae deposited in this Museum are listed; names are recorded, most of them represented by name-bearing types (primary types). The specific and subspecific names are alphabetically ordered in a single list, followed by the generic names (and subgeneric ones, if they were stated) spelled as they were published; later combinations and/ or current binomina are mentioned insofar these are known to the authors. Two lists are added: 2. Specimens labeled as types of names not found in the literature and probably never published, or published as nomina nuda; and 3. Specimens labeled as types, but not originally designated as such. An appendix provides a systematically arranged list of all names discussed, with indication of where they are discussed in the text.